2020
DOI: 10.4049/jimmunol.1900793
|View full text |Cite
|
Sign up to set email alerts
|

CARD9-Associated Dectin-1 and Dectin-2 Are Required for Protective Immunity of a Multivalent Vaccine against Coccidioides posadasii Infection

Abstract: This information is current as Infection posadasii Coccidioides Multivalent Vaccine against Are Required for Protective Immunity of a CARD9-Associated Dectin-1 and Dectin-2 Hung

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 66 publications
3
46
0
Order By: Relevance
“…To bridge this gap, transgenic HLA mice were applied as reliable animal models in pre-clinical investigation of vaccines (44). For example, a vaccine against Coccidioides posadasii was generated using human Th17-driven epitopes (45), and its protective effect was evaluated in humanized HLA-DR4 transgenic mice (46). Adequate investments are needed to evaluate the efficacy of PVAC in HLA class I and class II humanized transgenic mice in order to develop a human vaccine against PA in the future.…”
Section: Discussionmentioning
confidence: 99%
“…To bridge this gap, transgenic HLA mice were applied as reliable animal models in pre-clinical investigation of vaccines (44). For example, a vaccine against Coccidioides posadasii was generated using human Th17-driven epitopes (45), and its protective effect was evaluated in humanized HLA-DR4 transgenic mice (46). Adequate investments are needed to evaluate the efficacy of PVAC in HLA class I and class II humanized transgenic mice in order to develop a human vaccine against PA in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroconidia are the infectious propagules of Coccidioides. Infection of murine models through intranasal delivery is the preferred and widely used method to understand Coccidioides pathology (Campuzano et al, 2020;Castro-Lopez & Hung, 2017;Hayden et al, 2019;Mead, Roe, et al, 2020;Viriyakosol, Kapoor, et al, 2019). Susceptibility to Coccidioides varies among mouse strains, with studies having shown that C57BL/6 and BALB/c mice are highly susceptible and that DBA/2 mice are more resistant (Kirkland & Fierer, 1983).…”
Section: Intranasal Infection Of Murine Modelsmentioning
confidence: 99%
“…This is then incorporated into glucan–chitin particles derived from Rhodotorula mucilaginous , which acts as the adjuvant. Preliminary studies in mice have shown protection against strains of both C. immitis and C. posadasii [ 90 ], stimulation of the Th1/Th17 pathway [ 91 ], and activation of the CARD9 dectin-1 and dectin-2 signaling pathways [ 92 ]. Finally, no significant toxicity has been seen in a human liver cell line (HepG2) (personal communication, C-Y Hung).…”
Section: Vaccinesmentioning
confidence: 99%